Implementation of Demonstration Strategy in Fiqh Subject in Class VIII MTs Al-Ghozali Jatibarang - Didik Himmawan; Tamirih (Quality : Journal Of Education, Arabic And Islamic Studies, 2025)
In essence, education is an important thing for the Indonesian nation. Moreover, with the effectiveness of learning in the classroom so that understanding of the material, especially the subject of fiqh, is greater. The study included qualitative descriptive research because the object of the study was class VIII students at MTs Jatibarang. While the method used was the demonstration and lecture method, using this method gave a lot of positive responses from students and could also make the learning method more effective. The results of this study itself show that students in class VIII MTs can understand what is conveyed in the subject of fiqh.